Are intrinsic neural timescales related to sensory processing? Evidence from abnormal behavioral states - Zilio, Federico; Gomez-Pilar, Javier; Cao, Shumei; Zhang, Jun; Zang, Di; Qi, Zengxin; Tan, Jiaxing; Hiromi, Tanigawa; Wu, Xuehai; Fogel, Stuart; Huang, Zirui; Hohmann, Matthias R.; et al. (NeuroImage (Orlando, Fla.), 2021)
•EEG resting-state shows a hierarchy of intrinsic neural timescales.•Sensory deficits as in disorders and alterations of consciousness lead to prolonged intrinsic neural timescales.•Clinical conditions with motor deficits do not show changes in intrinsic neural timescales. The brain exhibits a complex temporal structure which translates into a hierarchy of distinct neural timescales. An open question is how these intrinsic timescales are related to sensory or motor information processing and whether these dynamics have common patterns in different behavioral states. We address these questions by investigating the brain's intrinsic timescales in healthy controls, motor (amyotrophic lateral sclerosis, locked-in syndrome), sensory (anesthesia, unresponsive wakefulness syndrome), and progressive reduction of sensory processing (from awake states over N1, N2, N3). We employed a combination of measures from EEG resting-state data: auto-correlation window (ACW), power spectral density (PSD), and power-law exponent (PLE). Prolonged neural timescales accompanied by a shift towards slower frequencies were observed in the conditions with sensory deficits, but not in conditions with motor deficits. Our results establish that the spontaneous activity's intrinsic neural timescale is related to the neural capacity that specifically supports sensory rather than motor information processing in the healthy brain. [Display omitted]